(untitled) (Fiep Bulletin - online, 2020)
Gelroid fibro edema is classified as a disorder in the metabolism of subcutaneous tissue, which leads to a change in the women’s body and as a treatment therapy, there is manual lymphatic drainage. Objective: To analyze the efficacy of manual lymphatic drainage in the treatment of fibroid edema. Methodology: Scientific articles were used in Portuguese and English, from 2010 to 2018. Results: A total of 370 articles were found, being screened and the articles obtained by data analysis were only 7, which were exposed in a table containing Author, Title, Description and Year. Conclusion: The efficacy of manual lymphatic drainage in the treatment of fibroid edema in women was evident. However, such protocol should be associated with a quality of life aiming at a better prognosis of aesthetic dysfunction.